Study the Antioxidant (Eurasian Journal of Research, Development and Innovation, 2024)
Many substances consumed by man either through foods, drinks and inhalation, even effect of exogenous material (ultraviolet radiation) on the skin may be destructive to the health and thus, shortening the life span of man. Free radicals when generated in the body system of man causes damage to which eventually leads to death at shorter time (Borek, 1991). Continuous usage of the same vegetable oil which is not even properly stored and re-using the already fried oil (rancid) lead to generation of free radicals through lipid peroxidation. The reasons sometimes could be for economic reason but then it is highly damaging to the health. Smoking and chronic alcoholism is socio-cultural problem in the world today because uncontrolled cigarette smoke intake reduces the level of many important antioxidants in the serum, which is detrimental to the health (Cheremisinoff, 1989). Report has shown that proper intake of antioxidant will help quench all these inevitably free radicals in the body thus, improving the health by lowering the risk of various diseases such as cancer. Antioxidants are also important in body lotions creams, so as to protect the skin from sun exposure and decrease skin roughness, wrinkles depth, ultraviolet induced skin cancer and skin swelling from sunlight. To cap it up, there is need for proper orientation on the necessity of proper intake of balance diet which will definitely supply the much needed antioxidants. The RDA has been previewed therefore, people will have lower health risks and tend to live longer and have fewer disabilities.